MenACWY-CRM conjugate vaccine booster dose given 4–6 years after priming: Results from a phase IIIb, multicenter, open label study in adolescents and adults. Issue 42 (30th September 2019) - Tipton, Mary; Daly, Wendy; Senders, Shelly; Block, Stanley L.; Lattanzi, Maria; Mzolo, Thembile; Barbi, Silvia; Pellegrini, Michele; Keshavan, Pavitra
Highlights: A booster MenACWY-CRM dose was given 4–6 years post-MenACWY-CRM or -MenACWY-D priming. The immune response to the booster was sufficient after priming with either vaccine. A least 93.2% of primed participants had seroresponse for each vaccine serogroup at 28 days after the booster dose. An anamnestic response was seen within 5 days after the booster dose. The booster MenACWY-CRM dose had a clinically acceptable safety profile. Abstract: Background: Vaccination strategies against bacterial meningitis vary across countries. In the United States, a single dose of quadrivalent meningococcal conjugate vaccine (MenACWY) is recommended at 11–12 years of age, with a booster dose approximately 5 years later. We assessed immune responses to a booster dose of MenACWY-CRM vaccine after priming with MenACWY-CRM or MenACWY-D vaccines in adolescents and adults. Methods: In this phase IIIb, multicenter, open-label study, healthy 15–55-year-olds, who received MenACWY-CRM (N = 301) or MenACWY-D (N = 300) 4–6 years earlier or were meningococcal vaccine-naïve (N = 100), received one MenACWY-CRM vaccine dose. Immunogenicity was evaluated pre-vaccination, 3 or 5 days post-vaccination (sampling subgroups), and 28 days post-vaccination by serum bactericidal activity assay using human complement (hSBA). After vaccination, participants were monitored for 7 days for reactogenicity, 29 days for unsolicited adverse events (AEs), and 181 days for serious AEs and medically-attended AEs. Results: Sufficiency of the immune response to a MenACWY-CRM booster dose was demonstrated; the lower limit of the 1-sided 97.5% confidence interval for percentages of participants with hSBA seroresponse at 28 days post-vaccination was >75% for each serogroup in those primed with either the MenACWY-CRM or MenACWY-D vaccine. Seroresponse was observed in ≥93.24% of primed participants and ≥35.87% of naïve participants 28 days post-vaccination. At 5 days post-booster, among primed participants, hSBA titers ≥1:8 were achieved in ≥47.14% of participants for MenA and in ≥85.52% of participants for MenC, MenW and MenY, and 3.25- to 8.59-fold increases in hSBA geometric mean titers against each vaccine serogroup were observed. No safety concerns were raised throughout the 6-month follow-up period. Conclusions: A booster dose of the MenACWY-CRM vaccine induced a robust and rapid anamnestic response in adolescents and adults, irrespectively of either MenACWY-CRM or MenACWY-D vaccine administered 4–6 years earlier, with an acceptable clinical safety profile. ClinicalTrials.gov registration: NCT02986854 . An Audio Summary linked to this article that can be found on Figshare https://figshare.com/articles/MenACWY-CRM_conjugate_vaccine_booster_dose_given_4_6_years_after_priming_Results_from_a_phase_IIIb_multicenter_open_label_study_in_adolescents_and_adults_mp4/11823048